Style-Shifting in Classroom Discourse among Senior High School English Language Teachers - Valdez-Howarth, Marjorie V; Jimenez, Jessica J (ASEAN Multidisciplinary Research Journal, 2019)
This study draws from the field of Stylistics relative to its investigation of a stylistic feature in the classroom teaching discourse of ESL (English as a second language) teachers, specifically their peculiar use of certain modes of style shifting. The participants of the study are male and female Senior High School (SHS) English Language Teachers (ELTs) who are affiliated to 16 Public Schools that are under the jurisdiction of DepEd Pangasinan-1 Schools Division. Data sets were sourced from the respondents using a battery of survey and perceptual questionnaires that are researcher developed, although theory-informed and subjected to content validation by academic experts prior to their utilization in gathering relevant data. Various modes of quantitative treatment were used to analyze the sets of data, which include quasi-statistical processes. The study found that all the ELTs, both male and female, practice style shifting at a “high” extent in their classroom EL teaching discourse. This finding cuts across the different aspects of teaching discourse, to wit: “teaching course content”, “calling for students’ participation”, “giving instructions for learning activities”, and “responding to students’ queries and clarifications”. As to the ELTs’ preferred mode of style shifting, a number ELTs manifest a “significant preference” for either code switching or code mixing, although majority of them prefer “code switching”. Some ELTs have a balanced significant preference for both “code switching” and “code mixing”. Based on the findings and the conclusions of the study, the study recommends that style shifting practices which has become prevalent among ELTs must be duly noted by the school management who might consider the integration of style shifting as a matter of language strategies/practices in the teaching of English course, and prevent teachers’ random and unregulated use of style shifting when merely carried out in their personal discretion.